Analisis Gaya Bahasa Personifikasi dalam Kumpulan Cerpen Sepasang Sepatu Tua Karya Sapardi Djoko Damono - Fauziyah, Rahmah; Nugroho, Rudi Adi (Kajian Bahasa dan Sastra (KABASTRA), 2023)
Language style in short stories is an important element in building a unique story. The choice of language and story development in a collection of short stories of a pair of old shoes by Sapardi Djoko Damono has a deep meaning. One of them is the personification style used to describe various conditions and feelings. The disclosure of the contents of the short story collection book is wrapped in a distinctive language style. Deep messages can be felt from the use of a unique language style. It is not only the imagination in the story that is conveyed but also the feelings of the author that are poured out properly. The existence of phenomena related to current conditions is a special attraction because it is presented in a unique style of language. This study used a qualitative descriptive method with observing, note-taking and literature study techniques.